Influences of Ethnicity on Perceptions of Contraceptive Use in Postpartum Women With Unintended Pregnancies [26F]. Issue 1 (May 2017) - Skanes-DeVold, Heather; Benoit, Candace; Erby, Brittainy; Ochs, Katherine; Maxwell, Rose; Lindheim, Steven
Abstract : INTRODUCTION: Unintended pregnancies (UIP) account for nearly 50% of pregnancies. Studies suggest that minority women are less compliant and less likely to use contraception. We assessed knowledge and attitudes associated with pre- and postpartum contraception use in women with UIP. METHODS: A 21-question survey was given to 350 full-term women between the ages of 18 and 40 within 48 hours of delivery from August 2014 to August 2016. RESULTS: Of the 195 respondents, 56% were women with UIP. With regards to UIP, 42% were Caucasian (CA), 49% African American (AA), 3% Hispanic and 6% other. The latter two groups were excluded from analysis. CA and AA were similar in education level (61% vs 59% greater than high school), contraception access/insurance coverage (96% vs 96%), use prior to (61% vs 47%) and at the time of conception (14% vs 24%), P-NS. There was no difference in negative perceptions of contraception (CA- 42% and AA-49% P-NS), though weight gain was high in both (CA 72% vs AA 71%, P-NS). AA were less likely to identify benefits of contraception compared to CA (AA 81% vs CA 93%, P < .001), including a reduction in acne (AA 10% vs CA 39% P < .001) and prevention of further UIP (AA 46% vs CA 78%, P < .001). CONCLUSION: Understanding the disbelief among AA that birth control has non-contraceptive benefits in addition to effectively preventing pregnancy, may be the first step in the development of culturally targeted education and further aid in the reduction of disparities in UIP.